Kompetenzorientierte Lehrerbildung - Zur Gestaltung des Praxissemesters in wirtschaftspädagogischen Studiengängen - Kremer, H.-Hugo (Standardization, professionalizationn and the measurements)

Social Media: Potenziale und Herausforderungen für die berufliche Bildung - Kremer, H.-Hugo (Standardization, professionalization and the measurements)

Forschung in Innovationsarenen: Individuelle Förderung als Herausforderung in der Bildungsarbeit in der Ausbildungsvorbereitung an Berufskollegs - Kremer, H.-Hugo; Zoyke, A. (Facetten berufs- und wirtschaftspädagogischer Forschung. Grundlagen - Herausfoderungen - Perspektiven)

Exploring Personalized Learning in the Context of the Transition System, vol. 2. Opladen - Beutner, Marc; Kremer, H.-Hugo; Zoyke, A. (Transitions in Vocational Education, Research in Vocational Education)

Berufsbildung im Übergang - Kompetenzentwicklung in der Ausbildungsvorbereitung - Kremer, H.-Hugo (Kompetenzentwicklung in unterschiedlichen Lernkulturen)

Social Media: Potentials and Challenges for Vocational Education - Kremer, H.-Hugo (From Diagnostics to Learning Success. Proceedings in Vocational Education and Training)

Herausforderungen der Kompetenzorientierung in der Studienprogrammentwicklung - Brahm, Taiga; Jenert, Tobias (Zeitschrift für Hochschulentwicklung)
Kompetenzorientierung ist ein wichtiges aktuelles Ziel bei der Studienprogrammentwicklung. Allerdings ist die Umsetzung in der Praxis mit zwei wesentlichen Herausforderungen verbunden: So ist zum einen der Wechsel von disziplinären Inhalten hin zu Kompetenzen wenig intuitiv; zum anderen wird die Formulierung so genannter Learning Outcomes als administrative Übung betrachtet. An der Universität St. Gallen wurde ein systematischer Prozess für die Qualitätsentwicklung der Studienprogramme eingeführt. Im Beitrag wird dieser Prozess im Hinblick auf die Kompetenzorientierung reflektiert. Es erscheint wesentlich, den Programmen möglichst viel Freiraum auf ihrem Weg zur Kompetenzorientierung zu überlassen und sie auf diese Weise zu unterstützen.
Keywords: Kompetenzorientierung; Studienprogrammentwicklung; Hochschulentwicklung; Hochschule; Learning Outcomes

Ein e-Portfolio-Konzept zur Integration heterogener Lernvoraussetzungen und Studienerfahrungen in der Lehrerbildung - Jenert, Tobias; Brahm, Taiga (Journal für LehrerInnenbildung)
Die Auseinandersetzung mit Bildungstechnologien erfolgt häufig ausgehend von einem technologischen Trend bzw. einer Klasse innovativer Werkzeuge (bspw. mobile Technologien). Es geht dann darum, die Potenziale dieser Tools für das Lernen zu ergründen, also letztlich eine Passung zwischen den technologischen Möglichkeiten und pädagogisch-didaktischen Erfordernissen zu konstruieren. In diesem Beitrag kehren wir diese Perspektive um: Ausgehend von einer bestimmten pädagogischen Problemstellung - der Bearbeitung heterogener Lernvoraussetzungen und Studienerfahrungen in der Lehrerbildung - entwickeln wir unterschiedliche didaktische Handlungsoptionen. Am Ende entsteht ein Werkzeug, das sich in Design und Funktionsumfang auf den Kern der pädagogischen Zielsetzung beschränkt.
Keywords: Portfolio; Lehrerbildung; Wirtschaftspädagogik

How Business Students Attitudes towards their University and Studying Develop during the First Year: A Qualitative Longitudinal Study - Jenert, Tobias; Brahm, Taiga
The aim of this qualitative study is first to investigate the attitude development of students in their initial year at university. College effectiveness research has shown that attitudes towards studying as well as to one's university are key factors influencing student engagement. Up to now, little is known about the processes through which such attitudes develop. Based on the theory of planned behaviour (Ajzen & Fishbein, 1980), the study addresses this research gap in three parts: a) development paths of students' attitudes towards studying and the university; b) the normative behaviour of the fellow students as well as significant persons, c) university-related experiences during the first year influencing students' attitude development. To answer these research questions, a series of five interviews was conducted throughout the first year with a total of 13 first-year students at the University of St. Gallen/Switzerland. Data analysis was performed referring to the procedures suggested by Neale (2012) for qualitative longitudinal data. To master the challenge of displaying developments over time, graphical analysis was used to construct a case history (cf. Henderson, Holland et al., 2012) for each individual. Regarding the students' developments over time, the analysis shows the participants' attitudes towards the university became more differentiated over time. A second major result concerns frictions between students' own attitudes and what they perceive to be the dominant normative behaviour. It became obvious that this developmental process is influenced by concrete incidents students experience during the first year and thus, can be shaped by structural changes.
Keywords: student attitudes; qualitative research; longitudinal study; student motivation

On the assessment of attitudes towards the study process and the university: Attitudes towards the Study Environment Questionnaire (ASEQ) - Brahm, Taiga; Jenert, Tobias; Euler, Dieter
The purpose of the research was to develop and validate an instrument for the assessment of attitudes towards the study environment in higher education contexts. The questionnaire is designed to measure students' attitudes towards two particular objects: the university (or Higher Education Institution) and the process of studying. Five studies at two different universities were conducted to develop and validate the Attitudes towards the Study Environment Questionnaire (ASEQ). In total, 1640 students filled in the questionnaire. Reliability tests and exploratory factor analysis as well as confirmatory factor analysis showed satisfactory psychometric characteristics of the ASEQ. Each part of the questionnaire is internally consistent and construct validity of the scales is supported by correlations with other constructs as assumed by current theories: Positive attitudinal constructs (normative behavior, autonomy, joy, self-efficacy, and task value) are positively related to intrinsic motivation and the expected study performance while anxiety is negatively related to these constructs. Since attitudes towards the study situation are connected to student engagement and motivation, the study contributes to the theory of student learning by providing a validated instrument to assess attitudes. Thus, the ASEQ can support further research on student performance and development by providing an instrument for the hitherto neglected but nonetheless extremely relevant domain of attitudes. Also, the questionnaire can be used as a diagnostic instrument for higher education faculty and administration to trace students' attitudinal development over time - a factor of prime importance for student socialization during the introductory phase of studying.
Keywords: attitudes; teaching and learning; studying; higher education institution; theory of planned behavior; instrument development

A latent growth curve analysis of Business students' intrinsic and extrinsic motivation - Brahm, Taiga; Jenert, Tobias
The proposed paper aims to investigate the longitudinal development of students' motivation over the first year of their studies at a business school by using latent growth curve modeling. The study tackles the following core research questions: How do first-year university students' intrinsic and extrinsic vary over time? Which (motivational) factors are related to students' motivational development? Although motivational dispositions have been analyzed extensively in previous studies, their longitudinal development has hitherto not been examined in the higher education context. This longitudinal study is conducted at the University of St. Gallen in Switzerland. The current sample includes 280 first-year students who have been surveyed three times and who are representative of the first-year student population. Descriptive results show that prior to their studies, students were motivated most by intrinsic factors, however, extrinsic motivation was also quite high. Employing latent growth curve modeling, it could be shown that both intrinsic and extrinsic motivation decline significantly over the course of the first year (8 months). The study contributes to motivation theory by providing further insights into the development of academic motivation over time. Latent growth curve modeling as a method can be well used for longitudinal data analysis, thus, excluding measurement error from longitudinal data. Furthermore, the study supports educational developers by determining factors influencing students' motivational development.
Keywords: motivation; intrinsic motivation; extrinsic motivation; latent growth curve modeling; longitudinal data analysis; ASEQ; higher education; studying

Die Entwicklung studien-und hochschulbezogener Einstellungen an einer Wirtschaftsuniversität: eine qualitative Längsschnittstudie - Jenert, Tobias; Brahm, Taiga
Die vorliegende Untersuchung an der Universität St. Gallen soll Erkenntnisse über die Verläufe der Einstellungsveränderungen der Studierenden geben (vgl. Brahm & Jenert, 2012). Basierend auf der Theorie des geplanten Verhaltens (Ajzen & Fishbein, 1980) werden drei Forschungsfragen adressiert: (1) Gibt es typische Pfade der Einstellungsentwicklung? (2) Wie wird das normative Verhalten von Mitstudierenden und anderen Personen wahrgenommen? (3) Welche Erfahrungen beeinflussen die Entwicklung? Zur Beantwortung dieser Fragen wurde über das erste Studienjahr hinweg eine Interviewserie mit 13 Studierenden durchgeführt. Die Datenanalyse mithilfe grafischer Case Histories zeigt, dass die Einstellungen der Probanden über die Zeit differenzierter werden. Zudem gibt es Widersprüche zwischen den Einstellungen und dem wahrgenommenen normativen Verhalten. Dabei ist die Einstellungsentwicklung von konkreten Ereignissen geprägt und kann damit durch strukturelle Interventionen beeinflusst werden.
Keywords: student attitudes; theory of planned behaviour; Einstellungsentwicklung; student motivation

Eine strategische Perspektive auf die Qualitätsentwicklung in Studienumgebungen - Jenert, Tobias; Brahm , Taiga (Lehrforschung wird Praxis: Hochschuldidaktische Forschungsergebnisse und ihre Integration in die Praxis)

Die Erforschung von Lernkulturen an Hochschulen unter Nutzung komplementärer Zugänge: Erste Erfahrungen aus einem Forschungsprogramm - Jenert, Tobias; Gebhardt , Anja (Kompetenzentwicklung in unterschiedlichen Lernkulturen, Festschrift für Dieter Euler zum 60. Geburtstag)

A Tree-form Constant Market Share Model for Growth Causes in International Trade Based on Multi-level Classification - Feng, Yuanhua; Guo, Zhichao; Peitz, Christian (Journal of Industry, Competition and Trade)

Modeling of the impact of the financial crisis and China's accession to WTO on China's exports to Germany - Guo, Zhichao; Feng, Yuanhua (Economic Modelling)

Long-Memory Processes - Beran, Jan; Feng, Yuanhua; Ghosh, Sucharita; Kulik, Rafal

A Semi-APARCH approach for comparing long-term and short-term risk in Chinese financial market and in mature financial markets - Feng, Yuanhua; Sun, Lixin

Double-conditional smoothing of high-frequency volatility surface in a spatial multiplicative component GARCH with random effects - Feng, Yuanhua

Zero Overhead Runtime Monitoring - Wonisch, Daniel; Schremmer, Alexander; Wehrheim, Heike (Proceedings of the 11th International Conference on Software Engineering and Formal Methods (SEFM))
Runtime monitoring aims at ensuring program safety by monitoring the program's behaviour during execution and taking appropriate action before a program violates some property.Runtime monitoring is in particular important when an exhaustive formal verification fails. While the approach allows for a safe execution of programs, it may impose a significant runtime overhead.In this paper, we propose a novel technique combining verification and monitoring which incurs no overhead during runtime at all. The technique proceeds by using the inconclusive result of a verification run as the basis for transforming the program into one where all potential points of failure are replaced by HALT statements. The new program is safe by construction, behaviourally equivalent to the original program (except for unsafe behaviour),and has the same performance characteristics.

Reflection, abstraction and theorizing in design and development research - Gregor, Shirley; Müller, Oliver; Seidel, Stefan (European Conference on Information Systems)
Keywords: Abstraction; Affordances; Design Science Research; Design Theory; Information Systems Development; Reflection; Theorizing

Designing interaction routines in service networks: A modularity and social construction-based approach - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuss, Jens (Scandinavian Journal of Information Systems)
Keywords: Business process management; Conceptual modeling; Interaction routines; Modular design; Service networks; Social construction

Which Flows Are Hiding Behind My Wildcard Rule? Adding Packet Sampling to OpenFlow - Wette, Philip; Karl, Holger (Proceedings of the ACM SIGCOMM '13)
In OpenFlow [1], multiple switches share the same control plane which is centralized atwhat is called the OpenFlow controller. A switch only consists of a forwarding plane. Rules for forwarding individual packets (called ow entries in OpenFlow) are pushed from the controller to the switches. In a network with a high arrival rate of new ows, such as in a data center, the control trac between the switch and controller can become very high. As a consequence, routing of new ows will be slow. One way to reduce control trac is to use wildcarded ow entries. Wildcard ow entries can be used to create default routes in the network. However, since switches do not keep track of ows covered by a wildcard ow entry, the controller no longer has knowledge about individual ows. To nd out about these individual ows we propose an extension to the current OpenFlow standard to enable packet sampling of wildcard ow entries.

Bridging the gap between manufacturing and service through IT-based boundary objects - Becker, Jorg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuss, Jens (IEEE Transactions on Engineering Management)
Keywords: Action research; boundary spanning; business process management (BPM); service blueprinting; service networks

Verteilte Erstellung und Aktualisierung von Schlüsselservern in identitätsbasierten Verschlüsselungssystemen - Tezer, Alina

Vergleichsstudie zur Ausdrucksstärke von SMT-Solvern - Engelbrecht, Marco

Unlinkable content playbacks in a multiparty DRM system - Petrlic, Ronald; Sekula, Stephan (Data and Applications Security and Privacy XXVII)
We present a solution to the problem of privacy invasion in a multiparty digital rights management scheme. (Roaming) users buy content licenses from a content provider and execute it at any nearby content distributor. Our approach, which does not need any trusted third party - in contrast to most related work on privacy-preserving DRM - is based on a re-encryption scheme that runs on any mobile Android device. Only a minor security-critical part needs to be performed on the device's smartcard which could, for instance, be a SIM card.

Two-Stage Allocation Procedures - Röhl, Nils
Suppose some individuals are allowed to engage in different groups at the same time and they generate a certain welfare by cooperation. Finding appropriate ways for distributing this welfare is a non-trivial issue. The purpose of this work is to analyze two-stage allocation procedures where first each group receives a share of the welfare which is then, subsequently, distributed among the corresponding members. To study these procedures in a structured way, cooperative games and network games are combined in a general framework by using mathematical hypergraphs. Moreover, several convincing requirements on allocation procedures are discussed and formalized. Thereby it will be shown, for example, that the Position Value and iteratively applying the Myerson Value can be characterized by similar axiomatizations.

Towards practical privacy-preserving Digital Rights Management for Cloud Computing - Joshi, Nakul; Petrlic, Ronald (Proceedings of the 10th Annual IEEE Consumer Communications & Networking Conference (CCNC))
We propose a privacy-preserving digital rights management scheme for (future) cloud computing. Users buy software from software providers and execute it at computing centers. Our solution allows software providers to provide different license models, like execute at most n-times models. Users’ anonymity and unlinkability of actions are preserved and thus, profile building is not even possible under (a) pseudonym. Privacy protection in the honest-but-curious model is achieved by combining ring signatures with an anonymous recipient scheme.We employ secret sharing in a unique manner that allows the software provider to expose the user’s identity if the user commits fraud, e.g. by exceeding the execution limit n.

Towards Duality of Multicommodity Multiroute Cuts and Flows: Multilevel Ball-Growing - Kolman, Petr; Scheideler, Christian (Theory of Computing Systems)
An elementary h-route ow, for an integer h 1, is a set of h edge- disjoint paths between a source and a sink, each path carrying a unit of ow, and an h-route ow is a non-negative linear combination of elementary h-routeows. An h-route cut is a set of edges whose removal decreases the maximum h-route ow between a given source-sink pair (or between every source-sink pair in the multicommodity setting) to zero. The main result of this paper is an approximate duality theorem for multicommodity h-route cuts and ows, for h 3: The size of a minimum h-route cut is at least f=h and at most O(log4 k f) where f is the size of the maximum h-routeow and k is the number of commodities. The main step towards the proof of this duality is the design and analysis of a polynomial-time approximation algorithm for the minimum h-route cut problem for h = 3 that has an approximation ratio of O(log4 k). Previously, polylogarithmic approximation was known only for h-route cuts for h 2. A key ingredient of our algorithm is a novel rounding technique that we call multilevel ball-growing. Though the proof of the duality relies on this algorithm, it is not a straightforward corollary of it as in the case of classical multicommodity ows and cuts. Similar results are shown also for the sparsest multiroute cut problem.

Token Dissemination in Geometric Dynamic Networks - Abshoff, Sebastian; Benter, Markus; Cord-Landwehr, Andreas; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (Algorithms for Sensor Systems - 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics, ALGOSENSORS 2013, Sophia Antipolis, France, September 5-6, 2013, Revised Selected Papers)
We consider the k-token dissemination problem, where k initially arbitrarily distributed tokens have to be disseminated to all nodes in a dynamic network (as introduced by Kuhn et al., STOC 2010). In contrast to general dynamic networks, our dynamic networks are unit disk graphs, i.e., nodes are embedded into the Euclidean plane and two nodes are connected if and only if their distance is at most R. Our worst-case adversary is allowed to move the nodes on the plane, but the maximum velocity v_max of each node is limited and the graph must be connected in each round. For this model, we provide almost tight lower and upper bounds for k-token dissemination if nodes are restricted to send only one token per round. It turns out that the maximum velocity v_max is a meaningful parameter to characterize dynamics in our model.

Three-Valued Abstraction and Heuristic-Guided Refinement for Verifying Concurrent Systems - Timm, Nils
Software systems are playing an increasing role in our everyday life, and as the amount of software applications grows, so does their complexity and the relevance of their computations. Software components can be found in many systems that are charged with safety-critical tasks, such as control systems for aviation or power plants. Hence, software verification techniques that are capable of proving the absence of critical errors are becoming more and more important in the field software engineering. A well-established approach to software verification is model checking. Applying this technique involves an exhaustive exploration of a state space model corresponding to the system under consideration. The major challenge in model checking is the so-called state explosion problem: The state space of a software system grows exponentially with its size. Thus, the straightforward modelling of real-life systems practically impossible. A common approach to this problem is the application of abstraction techniques, which reduce the original state space by mapping it on a significantly smaller abstract one. Abstraction inherently involves a loss of information, and thus, the resulting abstract model may be too imprecise for a definite result in verification. Therefore, abstraction is typically combined with abstraction refinement: An initially very coarse abstract model is iteratively refined, i.e. enriched with new details about the original system, until a level of abstraction is reached that is precise enough for a definite outcome. Abstraction refinement-based model checking is fully automatable and it is considered as one of the most promising approaches to the state explosion problem in verification. However, it is still faced with a number of challenges. There exist several types of abstraction techniques and not every type is equally well-suited for all kinds of systems and verification tasks. Moreover, the selection of adequate refinement steps is nontrivial and typically the most crucial part of the overall approach: Unfavourable refinement decisions can compromise the state space-reducing effect of abstraction, and as a consequence, can easily lead to the failure of verification. It is, however, hard to predict which refinement steps will eventually be expedient for verification – and which not.

The Impact of Individual and Collective Reputation on Wine Prices: Empirical Evidence from the Mosel Valley - Frick, Bernd; Simmons, Robert (Journal of Business Economics)
Although of considerable practical importance, the separate impact of individual and collective reputation on firm performance (e.g. product prices) has not yet been convincingly demonstrated. We use a sample of some 70 different wineries offering more than 1,300 different Riesling wines from the Mosel valley to isolate the returns to individual reputation (measured by expert ratings in a highly respected wine guide) from the returns to collective reputation (measured by membership in two different professional associations where members are assumed to monitor each other very closely). We find that both effects are statistically significant and economically relevant with the latter being more important in quantitative terms than the former.

Symbiotic Coupling of P2P and Cloud Systems: The Wikipedia Case - Graffi, Kalman; Bremer, Lars (Proceedings of the International Conference on Communications (ICC'13))
Cloud computing offers high availability, dynamic scalability, and elasticity requiring only very little administration. However, this service comes with financial costs. Peer-to-peer systems, in contrast, operate at very low costs but cannot match the quality of service of the cloud. This paper focuses on the case study of Wikipedia and presents an approach to reduce the operational costs of hosting similar websites in the cloud by using a practical peer-to-peer approach. The visitors of the site are joining a Chord overlay, which acts as first cache for article lookups. Simulation results show, that up to 72% of the article lookups in Wikipedia could be answered by other visitors instead of using the cloud.

Statistisches Planen von Aktionen für autonome mobile Roboter in realen Umgebungen - Bieshaar, Maarten

SimuLizar: Design-Time modeling and Performance Analysis of Self-Adaptive Systems - Becker, Matthias; Becker, Steffen; Meyer, Joachim (Proceedings of the Software Engineering Conference (SE))
Modern software systems adapt themselves to changing environments, to meet quality-of-service requirements, such as response time limits. The engineering of the system’s self-adaptation logic does not only require new modeling methods, but also new analyzes of transient phases. Model-driven software performance engineering methods already allow design-time analysis of steady states of non-adaptive system models. In order to validate requirements for transient phases, new modeling and analysis methods are needed. In this paper, we present SimuLizar, our initial model-driven approach to model self-adaptive systems and analyze the performance of their transient phases. Our evaluation of a load balancer toy example shows the applicability of our modeling approach. Additionally, a comparison of our performance analysis with a prototypical implementation of our example system shows that the prediction accuracy is sufficient to identify unsatisfactory self-adaptations.

Service Matching under Consideration of Explicitly Specified Service Variants - Platenius, Marie Christin; von Detten, Markus; Gerth, Christian; Schäfer, Wilhelm; Engels, Gregor (IEEE 20th International Conference on Web Services (ICWS 2013))
One of the main ideas of Service-Oriented Computing (SOC) is the delivery of flexibly composable services provided on world-wide markets. For a successful service discovery,service requests have to be matched with the available service offers. However, in a situation in which no service that completely matches the request can be discovered, the customer may tolerate slight discrepancies between request and offer. Some existing fuzzy matching approaches are able to detectsuch service variants, but they do not allow to explicitly specify which parts of a request are not mandatory. In this paper, we improve an existing service matching approach based onVisual Contracts leveraging our preliminary work of design pattern detection. Thereby, we support explicit specifications of service variants and realize gradual matching results that can be ranked in order to discover the service offer that matches a customer’s request best.

Semi-Automated Software Composition Through Generated Components - Mohr, Felix; Kleine Büning, Hans (Proceedings of the 15th International Conference on Information Integration and Web-based Applications & Services (iiWAS))
Software composition has been studied as a subject of state based planning for decades. Existing composition approaches that are efficient enough to be used in practice are limited to sequential arrangements of software components. This restriction dramatically reduces the number of composition problems that can be solved. However, there are many composition problems that could be solved by existing approaches if they had a possibility to combine components in very simple non-sequential ways. To this end, we present an approach that arranges not only basic components but also composite components. Composite components enhance the structure of the composition by conditional control flows. Through algorithms that are written by experts, composite components are automatically generated before the composition process starts. Therefore, our approach is not a substitute for existing composition algorithms but complements them with a preprocessing step. We verified the validity of our approach through implementation of the presented algorithms.

Growing existing customers' revenue streams through customer referral programs - Garnefeld, Ina; Eggert, Andreas; Helm, Sabrina V; Tax, Stephen S (Journal of Marketing)

Erfolgsfaktor Value-Based Selling—Verkaufen, wenn Kundenorientierung nicht zum Erfolg führt - Haas, Alexander; Eggert, Andreas; Terho, Harri; Ulaga, Wolfgang (Marketing Review St. Gallen)

Seitenkanalresistenz paarungsbasierter Kryptographie - Otte, Oliver

Security Proofs for Pairing-Based Cryptography in the Generic Group Model - Bobolz, Jan

Securing Critical Unattended Systems with Identity Based Cryptography - A Case Study - Blömer, Johannes; Günther, Peter; Krummel, Volker (Proceedings of the 5th International Conference on Mathematical Aspects of Computer and Information Sciences (MACIS))
Unattended systems are key ingredients of various critical infrastruc-tures like networks of self service terminals or automated teller machines.For cost and efficiency reasons they should mostly run autonomously.Unattended systems are attractive and lucrative targets for various kindsof attacks, including attacks on the integrity of their components and thecommunication between components. In this paper, we propose a gen-eral cryptographic framework to protect unattended systems. We alsodemonstrate that instantiating the framework with techniques from iden-tity based cryptography is particularly well-suited to efficiently secureunattended systems.

Individual determinants of work attendance: Evidence on the role of personality - St{\, Susi; Fahr, Rene (Applied Economics)

Scheduling Variants with Speed-Scaling via the Primal-Dual Approach - Knopf, Michael

Routing in heterogenen OpenFlow Netzwerken - Wallaschek, Felix

Arbeitskräftebedarf bei hoher Arbeitslosigkeit: ein ökonomisches Zuwanderungskonzept für Deutschland - Zimmermann, Klaus F; Bauer, Thomas K; Bonin, Holger; Fahr, Rene; Hinte, Holger

The impact of risk perception and risk attitudes on corrupt behavior: Evidence from a petty corruption experiment - Mir Djawadi, Behnud; Fahr, Rene

The impact of tax knowledge and budget spending influence on tax compliance - Djawadi, Behnud Mir; Fahr, Rene

Ressource-Optimized Deployment of Multi-Tier Applications - The Data Rate-Constrained Case - Robbert, Christoph

Reputationssysteme und Gerichtsverfahren als Wekzeuge zur Sicherstellung von Qualitätsstandards in Transaktionen - Terentjew, Artjom

Reengineering of Component-Based Software Systems in the Presence of Design Deficiencies - von Detten, Markus
The maintenance of component-based software systems requires up-to-date models of their concrete architecture, i.e. the architecture that is realised in the source code. These models help in systematically planning, analysing and executing typical reengineering activities. Often no or only outdated architectural models of such systems exist. Therefore, various reverse engineering methods have been developed which try to recover a system's components, subsystems and connectors. However, these reverse engineering methods are severely impacted by design deciencies in the system's code base, especially violations of the component encapsulation. As long as design deciencies are not considered in the reverse engineering process, they reduce the quality of the recovered component structures. Despite this impact of design deciencies, no existing architecture reconstruction approach explicitly integrates a systematic deciency detection and removal into the recovery process. Therefore, I have developed Archimetrix. Archimetrix is a tool-supported architecture reconstruction process. It enhances a clustering-based architecture recovery approach with an extensible, pattern-based deciency detection. After the detection of deciencies, Archimetrix supports the software architect in removing the de ciencies and provides the means to preview the architectural consequences of such a removal. I also provide a process to identify and formalise additional deciencies. I validated the approach on three case studies which show that Archimetrix is able to identify relevant deciencies and that the removal of these deciencies leads to an increased quality of the recovered architectures, i.e. they are closer to the corresponding conceptual architectures.

Reducing Nondeterminism in Automated Service Composition - Mohr, Felix; Lettmann, Theodor; Kleine Büning, Hans (Proceedings of the 6th International Conference on Service Oriented Computing and Applications (SOCA))
Automated service composition has been studied as a subject of state based planning for a decade. A great deal of service composition tasks can only be solved if concrete output values of the services are considered in the composition process. However, the fact that those values are not known before runtime leads to nondeterministic planning problems, which have proven to be notoriously difficult in practical automated service composition applications. Even though this problem is frequently recognized, it has still received remarkably few attention and remains unsolved.This paper shows how nondeterminism in automated service composition can be reduced. We introduce context rules as a means to derive semantic knowledge from output values of services. These rules enable us to replace nondeterministic composition operations by less nondeterministic or even completely deterministic ones. We show the validity of our solutions not only theoretically but also have evaluated them practically through implementation.

Reactive Planar Spanner Construction in Wireless Ad Hoc and Sensor Networks - Benter, Markus; Neumann, Florentin; Frey, Hannes (Proceedings of the 32nd IEEE International Conference on Computer Communications (INFOCOM))
Within reactive topology control, a node determines its adjacent edges of a network subgraph without prior knowledge of its neighborhood. The goal is to construct a local view on a topology which provides certain desired properties such as planarity. During algorithm execution, a node, in general, is not allowed to determine all its neighbors of the network graph. There are well-known reactive algorithms for computing planar subgraphs. However, the subgraphs obtained do not have constant Euclidean spanning ratio. This means that routing along these subgraphs may result in potentially long detours. So far, it has been unknown if planar spanners can be constructed reactively. In this work, we show that at least under the unit disk network model, this is indeed possible, by proposing an algorithm for reactive construction of the partial Delaunay triangulation, which recently turned out to be a spanner. Furthermore, we show that our algorithm is message-optimal as a node will only exchange messages with nodes that are also neighbors in the spanner. The algorithm’s presentation is complemented by a rigorous proof of correctness.

Programs from Proofs – A PCC Alternative - Wonisch, Daniel; Schremmer, Alexander; Wehrheim, Heike (Proceedings of the 25th International Conference on Computer Aided Verification (CAV))
Proof-carrying code approaches aim at safe execution of untrusted code by having the code producer attach a safety proof to the code which the code consumer only has to validate. Depending on the type of safety property, proofs can however become quite large and their validation - though faster than their construction - still time consuming. In this paper we introduce a new concept for safe execution of untrusted code. It keeps the idea of putting the time consuming part of proving on the side of the code producer, however, attaches no proofs to code anymore but instead uses the proof to transform the program into an equivalent but more eﬃciently veriﬁable program. Code consumers thus still do proving themselves, however, on a computationally inexpensive level only. Experimental results show that the proof eﬀort can be reduced by several orders of magnitude, both with respect to time and space.

Profitable Scheduling on Multiple Speed-Scalable Processors - Kling, Peter; Pietrzyk, Peter (Proceedings of the 25th ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
We present a new online algorithm for profit-oriented scheduling on multiple speed-scalable processors.Moreover, we provide a tight analysis of the algorithm's competitiveness.Our results generalize and improve upon work by \citet{Chan:2010}, which considers a single speed-scalable processor.Using significantly different techniques, we can not only extend their model to multiprocessors but also prove an enhanced and tight competitive ratio for our algorithm.In our scheduling problem, jobs arrive over time and are preemptable.They have different workloads, values, and deadlines.The scheduler may decide not to finish a job but instead to suffer a loss equaling the job's value.However, to process a job's workload until its deadline the scheduler must invest a certain amount of energy.The cost of a schedule is the sum of lost values and invested energy.In order to finish a job the scheduler has to determine which processors to use and set their speeds accordingly.A processor's energy consumption is power $\Power{s}$ integrated over time, where $\Power{s}=s^{α}$ is the power consumption when running at speed $s$.Since we consider the online variant of the problem, the scheduler has no knowledge about future jobs.This problem was introduced by~\citet{Chan:2010} for the case of a single processor.They presented an online algorithm which is $α^{α}+2eα$-competitive.We provide an online algorithm for the case of multiple processors with an improved competitive ratio of $α^{α}$.

Born in the GDR: Imprinting, Structural Inertia and the Survival Chances of Organizations - Oertel, Simon; Thommes, Kirsten; Walgenbach, Peter (Academy of Management Proceedings)

The after effects of strikes on team collaboration-experimental evidence - Thommes, Kirsten; Akkerman, Agnes; Vyrastekova, Jana (Academy of Management Proceedings)

Berufsorientierung, Gewaltsensibilisierung und Kompetenzentwicklung - Konzepte zur beruflichen Bildung im JUngtätervollzug

Didaktik beruflicher Bildung - Kremer, H.-Hugo; Fischer, M.; Tramm, T. (bwp@ Berufs- und Wirtschaftspädagogik - online)

Standardization, professionalization and the measurements

Evidences of defect contribution in magnetically ordered Sm-implanted GaN - Lo, Fang-Yuh; Guo, Jhong-Yu; Huang, Cheng-De; Chou, Kai-Chieh; Liu, Hsiang-Lin; Ney, Verena; Ney, Andreas; Chern, Ming-Yau; Shvarkov, Stepan; Reuter, Dirk; Wieck, Andreas D.; Pezzagna, Sébastien; et al. (Current Applied Physics)

Combined influence of Coulomb interaction and polarons on the carrier dynamics in InGaAs quantum dots - Steinhoff, A.; Kurtze, H.; Gartner, P.; Florian, M.; Reuter, Dirk; Wieck, A. D.; Bayer, M.; Jahnke, F. (Physical Review B)

Picosecond real-space imaging of electron spin diffusion in GaAs - Henn, T.; Kiessling, T.; Ossau, W.; Molenkamp, L. W.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Hot carrier effects on the magneto-optical detection of electron spins in GaAs - Henn, T.; Heckel, A.; Beck, M.; Kiessling, T.; Ossau, W.; Molenkamp, L. W.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Magneto-optical studies of Gd-implanted GaN: No spin alignment of conduction band electrons - Buß, J. H.; Rudolph, J.; Shvarkov, S.; Semond, F.; Reuter, Dirk; Wieck, A. D.; Hägele, D. (Applied Physics Letters)

The effect of (NH4)2Sxpassivation on the (311)A GaAs surface and its use in AlGaAs/GaAs heterostructure devices - Carrad, D J; Burke, A M; Reece, P J; Lyttleton, R W; Waddington, D E J; Rai, A; Reuter, Dirk; Wieck, A D; Micolich, A P (Journal of Physics: Condensed Matter)

Spin relaxation length in quantum dot spin LEDs - Höpfner, Henning; Fritsche, Carola; Ludwig, Arne; Ludwig, Astrid; Stromberg, Frank; Wende, Heiko; Keune, Werner; Reuter, Dirk; Wieck, Andreas D.; Gerhardt, Nils C.; Hofmann, Martin R. (physica status solidi (c))

Frequency-Stabilized Source of Single Photons from a Solid-State Qubit - Prechtel, Jonathan H.; Kuhlmann, Andreas V.; Houel, Julien; Greuter, Lukas; Ludwig, Arne; Reuter, Dirk; Wieck, Andreas D.; Warburton, Richard J. (Physical Review X)

Biexcitons in semiconductor quantum dot ensembles - Moody, Galan; Singh, Rohan; Li, Hebin; Akimov, Ilya A.; Bayer, Manfred; Reuter, Dirk; Wieck, Andreas D.; Bracker, Allan S.; Gammon, Daniel; Cundiff, Steven T. (physica status solidi (b))

High-resolution mass spectrometer for liquid metal ion sources - Wortmann, Martin; Ludwig, Arne; Meijer, Jan; Reuter, Dirk; Wieck, Andreas D. (Review of Scientific Instruments)

Charge noise and spin noise in a semiconductor quantum device - Kuhlmann, Andreas V.; Houel, Julien; Ludwig, Arne; Greuter, Lukas; Reuter, Dirk; Wieck, Andreas D.; Poggio, Martino; Warburton, Richard J. (Nature Physics)

A dark-field microscope for background-free detection of resonance fluorescence from single semiconductor quantum dots operating in a set-and-forget mode - Kuhlmann, Andreas V.; Houel, Julien; Brunner, Daniel; Ludwig, Arne; Reuter, Dirk; Wieck, Andreas D.; Warburton, Richard J. (Review of Scientific Instruments)

Software Engineering for Self-Adaptive Systems: A Second Research Roadmap - de Lemos, Rogrio; Giese, Holger; A. Müller, Hausi; Shaw, Mary; Andersson, Jesper; Litoiu, Marin; Schmerl, Bradley; Tamura, Gabriel; M. Villegas, Norha; Vogel, Thomas; Weyns, Danny; Baresi, Luciano; et al. (Software Engineering for Self-Adaptive Systems II)

Leichtgewichtige Traceability im agilen Entwicklungsprozess am Beispiel von Scrum - Bouillon, Elke; Güldali, Baris; Herrmann, Andrea; Keuler, Thorsten; Moldt, Daniel; Riebisch, Matthias (Softwaretechnik-Trends)

Testen bei Migrationsprojekten - Grieger, Marvin; Güldali, Baris; Sauer, Stefan; Mlynarski, Michael (OBJEKTspektrum (Online Themenspecials))

Maßgeschneidert und werkzeugunterstützt Entwickeln angepasster Requirements Engineering-Methoden - Fazal-Baqaie, Masud; Güldali, Baris; Luckey, Markus; Sauer, Stefan; Spijkerman, Michael (OBJEKTspektrum (Online Themenspecials))

Editorial - Engels, Gregor; Luckey, Markus (Computer Science - Research and Development)

Informationstechnik spart Ressourcen - Engels, Gregor; Gerth, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Müller, Wolfgang; Sauer, Stefan (Forschungsforum Paderborn)

Detection and Resolution of Conflicting Change Operations in Version Management of Process Models - Gerth, Christian; Küster, Jochen; Luckey, Markus; Engels, Gregor (Software and Systems Modeling)

Wirtschaftlichkeitsberechnung für MBT: Wann sich modellbasiertes Testen lohnt - Faragó, David; Törsel, Arne-Michael; Mlynarski, Michael; Weißleder, Stephan; Güldali, Baris; Brandes, Christian (OBJEKTspektrum)
Modellbasiertes Testen verspricht potenziell eine höhere Effizienz und Effektivität im Testprozess. Ob im eigenen Kontext der Einsatz wirtschaftlich ist, ist jedoch häufig unklar. Dieser Beitrag analysiert systematisch Kosten- und Nutzenfaktoren und stellt ein Verfahren zur Abschätzung der Wirtschaftlichkeit des modellbasierten Testens vor. Anhand eines Beispiels wird der Ablauf veranschaulicht.

Spin injection, transport, and relaxation in spin light-emitting diodes: magnetic field effects - Höpfner, Henning; Fritsche, Carola; Ludwig, Arne; Ludwig, Astrid; Stromberg, Frank; Wende, Heiko; Keune, Werner; Reuter, Dirk; Wieck, Andreas D.; Gerhardt, Nils C.; Hofmann, Martin R. (Spintronics VI)

Spin relaxation length in quantum dot spin LEDs - Höpfner, Henning; Fritsche, Carola; Ludwig, Arne; Ludwig, Astrid; Stromberg, Frank; Wende, Heiko; Keune, Werner; Reuter, Dirk; Wieck, Andreas D.; Gerhardt, Nils C.; Hofmann, Martin R. (physica status solidi (c))

Influence of recombination center interaction on the photoluminescence of AlGaAs/GaAs heterostructures - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

Hanle effect in (In,Ga)As quantum dots: Role of nuclear spin fluctuations - Kuznetsova, M. S.; Flisinski, K.; Gerlovin, I. Ya.; Ignatiev, I. V.; Kavokin, K. V.; Verbin, S. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Origins of conductance anomalies in ap-type GaAs quantum point contact - Komijani, Y.; Csontos, M.; Ihn, T.; Ensslin, K.; Meir, Y.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Grazing-incidence X-ray diffraction of single GaAs nanowires at locations defined by focused ion beams - Bussone, Genziana; Schott, Rüdiger; Biermanns, Andreas; Davydok, Anton; Reuter, Dirk; Carbone, Gerardina; Schülli, Tobias U.; Wieck, Andreas D.; Pietsch, Ullrich (Journal of Applied Crystallography)

Influence of surface states on quantum and transport lifetimes in high-quality undoped heterostructures - Wang, D. Q.; Chen, J. C. H.; Klochan, O.; Das Gupta, K.; Reuter, Dirk; Wieck, A. D.; Ritchie, D. A.; Hamilton, A. R. (Physical Review B)

Scaling of the Kondo zero-bias peak in a hole quantum dot at finite temperatures - Klochan, O.; Micolich, A. P.; Hamilton, A. R.; Reuter, Dirk; Wieck, A. D.; Reininghaus, F.; Pletyukhov, M.; Schoeller, H. (Physical Review B)

Hot carrier effects on the magneto-optical detection of electron spins in GaAs - Henn, T.; Heckel, A.; Beck, M.; Kiessling, T.; Ossau, W.; Molenkamp, L. W.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Many-body correlations of electrostatically trapped dipolar excitons - Schinner, G. J.; Repp, J.; Schubert, E.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Govorov, A. O.; Holleitner, A. W.; Kotthaus, J. P. (Physical Review B)

Optical Spectroscopy of Spin Noise - Zapasskii, V. S.; Greilich, A.; Crooker, S. A.; Li, Yan; Kozlov, G. G.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review Letters)

Confinement and Interaction of Single Indirect Excitons in a Voltage-Controlled Trap Formed Inside Double InGaAs Quantum Wells - Schinner, G. J.; Repp, J.; Schubert, E.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Govorov, A. O.; Holleitner, A. W.; Kotthaus, J. P. (Physical Review Letters)

Temperature dependence of hole spin coherence in (In,Ga)As quantum dots measured by mode-locking and echo techniques - Varwig, S.; René, A.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Aharonov–Bohm rings with strong spin–orbit interaction: the role of sample-specific properties - Nichele, F; Komijani, Y; Hennel, S; Gerl, C; Wegscheider, W; Reuter, Dirk; Wieck, A D; Ihn, T; Ensslin, K (New Journal of Physics)

On the annealing mechanism of AuGe/Ni/Au ohmic contacts to a two-dimensional electron gas in GaAs/AlxGa1−xAs heterostructures - Koop, E J; Iqbal, M J; Limbach, F; Boute, M; van Wees, B J; Reuter, Dirk; Wieck, A D; Kooi, B J; van der Wal, C H (Semiconductor Science and Technology)

Correlation and dephasing effects on the non-radiative coherence between bright excitons in an InAs QD ensemble measured with 2D spectroscopy - Moody, G.; Singh, R.; Li, H.; Akimov, I.A.; Bayer, M.; Reuter, Dirk; Wieck, A.D.; Cundiff, S.T. (Solid State Communications)

Anisotropic Zeeman shift in p-type GaAs quantum point contacts - Komijani, Y.; Csontos, M.; Shorubalko, I.; Zülicke, U.; Ihn, T.; Ensslin, K.; Reuter, Dirk; Wieck, A. D. (EPL (Europhysics Letters))

Fifth-order nonlinear optical response of excitonic states in an InAs quantum dot ensemble measured with two-dimensional spectroscopy - Moody, G.; Singh, R.; Li, H.; Akimov, I. A.; Bayer, M.; Reuter, Dirk; Wieck, A. D.; Cundiff, S. T. (Physical Review B)

Confinement Effects on Biexciton Binding in Semiconductor Quantum Dots Measured with 2D Coherent Spectroscopy - Moody, G.; Singh, R.; Li, H.; Akimov, I. A.; Bayer, M.; Reuter, Dirk; Wieck, A. D.; Bracker, A. S.; Gammon, D.; Cundiff, S. T. (CLEO: 2013)